Application of dose response model for infection on selected case of oral mouth wash product - Mostafa Eissa (Shiraz University of Medical Sciences, 2016)
Microbial contamination of pharmaceutical products constitutes a great concern for stakeholders and professionals in the field. Special attention is brought to multidose medicinal products with considerable water activities (aw). Such pharmaceutical products are prone to microbial spoilage with serious consequences on patients' health and even their lives. The current investigation aimed to study new approach in the risk assessment of the contamination of oral antiseptic mouthwash in a quantitative manner using dose-response model of microbial infection. The present study combines both preservative efficacy test (PET) results with specific dose-response model of indicator bacteria. The risk was assessed at its maximum level using the worst case scenario of repeated contamination of the medicine bottle with each use. The indicator microbe selected was Escherichia coli with two models: exponential and beta Poisson based on antimicrobial efficacy test (AET) results. The mouthwash met the acceptance criteria of USP<51> PET, with notably strong effect on bacteria and yeast (not recovered from culture media) at any testing points (14 and 28 days). On the other hand, Aspergillus brasiliensis showed significant reduction after 28 days only. The current investigation showed that repeated product contamination with each use increased the risk of infection and different contaminating varies of the same microbial species constituted various hazard levels, although the antimicrobial properties of the product were sufficiently strong against the dedicated microbe (>3.00 log reduction (LR)). The current study provided new insight for the conventional pharmacopeial AET and demonstrated the limitation of it.